The problems of manipulation and the apocalyptic paintings’ linguistic objectification in political advertising (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the problems of manipulating mass consciousness, carried out through the actualization of fear as a basic human emotion, examines the specificity of verbal apocalyptic paintings in political advertising.
Keywords: political advertisement; manipulation; fear